APLIKASI GAME WIN START LA BERBASIS ANDROID - Roiduddin Al Adib; Nurul Fuad; Retno Wardhani (Joutica, 2017)
Game is one of the entertainment that is fun and interesting way to spend leisure time or relieve boredom at the time of waiting, a variety of games or game has been created and produced many free or paid. Starting from a brain teaser game theme, sports, to adventure. An android based games can provide entertainment for players. The purpose of this study was to design and build a game that can be played in your spare time and eliminate boredom when waiting. The method used in designing and building this game is the method of "Multimedia Development". Stages in the process of this study is Phase Concept , Design , Material Collection and Testing. By using the Unity Game Engine programming language and Android SDK, will produce an android game titled "Application-Based Android Game Win Start" to increase knowledge in making games with the theme of brain teasers and applying the lessons of artificial intelligence (Playing Game) with a greedy algorithm, uses 2D graphics and is designed for a single player